منهج ابن جماعة في كتابه " المنهل الروي في مختصر علوم الحديث النبوي " - العبيد، محمد عبيد (جامعة القدس المفتوحة, 2016)
هذا بحث تكلمت فيه عن منهج ابن جماعة في كتابه المنهل الروي في مختصر علوم الحديث النبوي، بينت فيه مدى صلته بكتاب (علوم الحديث) لابن الصلاح، وطريقته في التقسيم، وكيفية إيراد مضمون الكتاب، والمسائل التي ناقشها مع ابن الصلاح، وعددت الفوائد التي زادها.
In the name of Allah, the Merciful, the Beneficent, all praise is for Allah the One who, by His bounty, all good deeds are accomplished. In this paper I wrote about the method used by Ibn Jama'a in his book Al - Manhal Al - Rawi, his method of classification and presentation in his book and along and his debate with Ibn Salah. I also enumerated the benefits that he added.
Keywords: علو الحديث النبوى -- رواية الحديث -- بن جماعة، بدر الدين أبو عبدالله محمد بن ابراهيم بن سعد الله، ت. 733 هـ. -- تراجم علماء الحديث